2011
DOI: 10.1101/gr.125088.111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the epigenetic landscape during erythroid differentiation after GATA1 restoration

Abstract: Interplays among lineage-specific nuclear proteins, chromatin modifying enzymes, and the basal transcription machinery govern cellular differentiation, but their dynamics of action and coordination with transcriptional control are not fully understood. Alterations in chromatin structure appear to establish a permissive state for gene activation at some loci, but they play an integral role in activation at other loci. To determine the predominant roles of chromatin states and factor occupancy in directing gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
178
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(191 citation statements)
references
References 64 publications
13
178
0
Order By: Relevance
“…These conserved sites included those potentially bound by the canonical regulators of erythroid differentiation GATA1, NF-E2 (represented by AP-1 sites in data analyzed), and KLF1/EKLF (represented by SP1 sites in data analyzed) (32). This is consistent with the notion that specific master transcriptional regulators of differentiation are critical for the process of erythropoiesis in both species (1,32,33).…”
Section: Global Gene Expression Changes During Erythroid Terminalsupporting
confidence: 73%
“…These conserved sites included those potentially bound by the canonical regulators of erythroid differentiation GATA1, NF-E2 (represented by AP-1 sites in data analyzed), and KLF1/EKLF (represented by SP1 sites in data analyzed) (32). This is consistent with the notion that specific master transcriptional regulators of differentiation are critical for the process of erythropoiesis in both species (1,32,33).…”
Section: Global Gene Expression Changes During Erythroid Terminalsupporting
confidence: 73%
“…It is important to note that several GATA1/2 ChIP-Seq studies have recently been completed in erythroid and megakaryocytic cells Fujiwara et al, 2009;Yu et al, 2009;Tijssen et al, 2011;Wu et al, 2011;Doré et al, 2012). These studies have revealed that GATA1/2 predominantly function from enhancer elements and bind relatively few promoters.…”
Section: V205mmentioning
confidence: 99%
“…number of multimeric complexes involving other TFs and can activate or repress target gene expression (29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Significancementioning
confidence: 99%